Work Environment And Job Satisfaction Affect Employee Performance At The Public Order Agency And Fire Department Of South Bengkulu Regency - Azahri, Beni; Afriani, Sulisti; Utama, Iswidana Putra (Utami Publisher, 2025)
This research uses quantitative research. The analytical method in this study uses Validity Test, Reliability Test, Classic Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient and hypothesis testing using t-test. The number of samples studied was 73 questionnaires to employees at the Public Order Agency (Satpol PP) and the Fire Department of South Bengkulu Regency. The results of the multiple linear regression analysis are the equation: Y = 13.604 + 0.262 X1 + 0.410 X2 + e, this describes a positive regression direction, meaning that the variables Work Environment (X1) and Job Satisfaction (X2) have a positive influence on Employee Performance (Y) in Satpol PP and Fire Department of South Bengkulu Regency. The value of the coefficient of determination from the calculation results using SPSS can be seen that the coefficient of determination value of R square is 0.800. This means that the value of Work Environment (X1) and Job Satisfaction (X2) has an effect on employee performance (Y) by 80% while the remaining 20% is influenced by other variables not examined in the study.